Annual high-dose vitamin D3and mental well-being: randomised controlled trial - Kerrie M. Sanders; Amanda L. Stuart; Elizabeth Williamson; Felice N. Jacka; Seetal Dodd; Geoffrey C. Nicholson; Michael Berk (2011)
Background Epidemiological evidence supports a relationship between vitamin D and mental well-being, although evidence from large-scale placebo-controlled intervention trials is lacking. Aims To examine if vitamin D supplementation has a beneficial effect on mood in community-dwelling older women; if a single annual large dose of vitamin D has a role in the prevention of depressive symptoms; and if there is an association between serum 25-hydroxyvitamin D levels and mental health. Method A double-blind, randomised, placebo-controlled trial of women aged 70 or older (the Vital D Study: ISRCTN83409867 and ACTR12605000658617). Participants were randomly assigned to receive 500 000 IU vitamin D 3 (cholecalciferol) orally or placebo every autumn/winter for 3–5 consecutive years. The tools utilised at various time points were the General Health Questionnaire, the 12-item Short Form Health Survey, the Patient Global Impression–Improvement scale and the WHO Well-Being Index. Serum 25-hydroxyvitamin D levels were measured in a subset of 102 participants. Results In this non-clinical population, no significant differences between the vitamin D and placebo groups were detected in any of the measured outcomes of mental health. Serum 25-hydroxyvitamin D levels in the vitamin D group were 41% higher than the placebo group 12 months following their annual dose. Despite this difference, scores from the questionnaires did not differ. Furthermore, there was no interaction between those on antidepressant/anxiety medication at baseline and the treatment groups. Conclusions The lack of improvement in indices of mental well-being in the vitamin D group does not support the hypothesis that an annual high dose of vitamin D 3 is a practical intervention to prevent depressive symptoms in older community-dwelling women.